Business networks and the moderating impact of innovation on business performance - Jordaan, Brigitta (My University, 2021)
South Africa faces frighteningly high levels of unemployment, inequality and poverty. Like many other emerging economies, the South African government has recognised the importance of entrepreneurial activity. It widely views SME's (Small or Medium-sized Enterprises) as the lynchpin to realising growth and expansion. However, a common challenge to the performance and growth of many SME's is the lack of access to resources. Additionally, as advancements in innovation have so rapidly evolved in recent years, a business's innovative capabilities have become just as crucial to its performance capabilities and sustaining a competitive advantage. This study mainly focused on investigating the extent to which networks, particularly supplier, consumer and competitor networks, moderated by innovation, impacted the financial performance of SME's in South Africa. Data collection from SME owners and managers throughout South Africa using self-administered surveys, distributed via Qualtrics. The results show that two supplier networks and consumer networks moderated by innovation significantly impact business performance. Consequently, no factors from the consumer networks construct were extracted in the EFA analysis to determine consumer networks' impact on business performance. As such, no conclusions could be determined in considering the consumer network's impact on firm performance. Findings suggest that the study be replicated with a significantly larger sample. It is also recommended that further research explores the extent to which network activities and network resources, when moderated by innovation, impacts business performance, with a view on measuring alternate performance metrics such as growth, market share and consumer and employee satisfaction and growth
A research report submitted to the Faculty of Commerce, Law and Management at the University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management (in Entrepreneurship and New Venture Creation), 2021
Keywords: Business networks; Innovation; Business performance; SMEs; Consumers; Suppliers; Competitors engagement and collaboration; SDG-8: Decent work and economic growth